Classroom Teachers' Views on the Use of Games in Teaching Turkish - Bay, Yalçin; Uğur, Emre (Fırat University, 2022)
In this study, "Opinions of Classroom Teachers on the Usage of Games in Teaching Turkish" were examined. The general purpose of the research is to determine the usability, benefits and limitations of games in teaching Turkish. Teachers' opinions about the use of games in Turkish lessons are important. Putting forward the opinions of teachers about who should prepare the games, at which grade levels and on which subjects, and which games are used more will constitute a resource to be used in teaching Turkish with games. The population of the study is composed of classroom teachers in the central district of Afyonkarahisar province, while the sample consists of 408 randomly selected classroom teachers in this population. The research was arranged according to the scanning model, and the personal information form and teacher questionnaire were used as data collection tools. Findings obtained as a result of the research show that; teachers benefit from games in teaching Turkish. Although this teaching method has its limitations, it is preferred that it is student-centered, provides active participation of students, abstracts concrete concepts, and improves problem solving skills.

Bu araştırmada “Türkçe Öğretiminde Oyunların Kullanımlarına İlişkin Sınıf Öğretmenlerinin Görüşleri” incelenmiştir. Araştırmanın genel amacı, oyunların Türkçe öğretiminde kullanılabilirliği, faydaları, sınırlılıklarının tespit edilmesidir. Öğretmenlerin Türkçe dersinde oyunların kullanımı konusundaki görüşleri önem taşımaktadır. Oyunların kim tarafından hazırlanması gerektiği, hangi sınıf düzeylerinde ve hangi konularda kullanılması gerektiği ve hangi oyunların daha çok kullanıldığına dair öğretmen görüşlerinin ortaya konulması, oyunla Türkçe öğretimi konusunda faydalanılacak bir kaynak oluşturacaktır. Araştırmanın evrenini Afyonkarahisar ili merkez ilçesindeki sınıf öğretmenleri oluştururken, örneklemini ise bu evrendeki random yolla seçilen 408 sınıf öğretmeni oluşturmaktadır. Yapılan araştırma tarama modeline göre düzenlenmiş olup veri toplama aracı olarak kişisel bilgiler formu ve öğretmen anketi kullanılmıştır. Araştırma sonucunda elde edilen bulgular göstermektedir ki; öğretmenler Türkçe öğretiminde oyunlardan yararlanmaktadır. Bu öğretim yönteminin sınırlılıkları olmakla birlikte, öğrenci merkezli olması öğrencilerin aktif katılımını sağlaması, somut kavramları soyutlaştırması, problem çözme becerilerini geliştirmesi yönüyle tercih edilmektedir.
Sınıf Öğretmenlerinin Türkçe Öğretiminde Oyunların Kullanımına İlişkin Görüşleri
Keywords: Other Fields of Education; Alan Eğitimleri